2016
DOI: 10.1021/acs.jafc.5b05442
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Synthesis of Benzenoid Compounds by the Yeast Hanseniaspora vineae Increases the Flavor Diversity of Wines

Abstract: Benzyl alcohol and other benzenoid-derived metabolites of particular importance in plants confer floral and fruity flavors to wines. Among the volatile aroma components in Vitis vinifera grape varieties, benzyl alcohol is present in its free and glycosylated forms. These compounds are considered to originate from grapes only and not from fermentative processes. We have found increased levels of benzyl alcohol in red Tannat wine compared to that in grape juice, suggesting de novo formation of this metabolite du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…All 14 S. cerevisiae industrial strains only showed one copy of ARO10 (Table S5). Further, ARO10 has been shown to be related to the production of benzyl alcohol in a putative metabolic pathway of mandelate (7). Therefore, this decarboxylase activity might be involved in the enhanced (more than two orders of magnitude) synthesis of benzylic alcohol in H. vineae compared to that in S. cerevisiae (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…All 14 S. cerevisiae industrial strains only showed one copy of ARO10 (Table S5). Further, ARO10 has been shown to be related to the production of benzyl alcohol in a putative metabolic pathway of mandelate (7). Therefore, this decarboxylase activity might be involved in the enhanced (more than two orders of magnitude) synthesis of benzylic alcohol in H. vineae compared to that in S. cerevisiae (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the first two esters are released in higher concentrations (2-7) than S. cerevisiae; by comparison, ethyl lactate is usually produced below the sensory threshold. Formation de novo of benzyl acetate and 2-phenylethyl acetate from sugars by the chorismate-prephenate pathway has been reported ( [36], Figure 3). It has been observed that nitrogen nutrition affected the formation of benzyl and 2-phenylethyl acetates.…”
Section: Influence Of Non-saccharomyces Yeasts On Wine Aromamentioning
confidence: 93%
“…High doses of diammonium phosphate (100-250 mg/L) inhibited the production of these phenylpropanoid compounds and negatively affected the global balance of aromatic esters [37]. Benzyl alcohol, precursor of benzyl acetate, can be obtained de novo without using grape precursors by 11 different H. vineae strains at concentrations 20-200 fold higher than with S. cerevisiae strains [36]. Regarding the H. vineae species, the main esters with sensory repercussion from its exometabolome are benzyl acetate, 2-phenylethyl acetate, ethyl lactate and 3-methylbutyl acetate [35].…”
Section: Influence Of Non-saccharomyces Yeasts On Wine Aromamentioning
confidence: 99%
“…At an industrial scale, Hanseniospora guilliermondii, Hanseniospora uvarum, and Hanseniospora vinae [130] are the most appropriate species to achieve these purposes [125]. The aroma improvements are explained from a chemical point of view due to the production of higher concentrations of 2-phenylethyl acetate [131,132], acetate esters such as isoamyl acetate [124,127,130,132,133], medium-chain fatty acid ethyl esters [134], benzenoids [135,136], and terpenes [125,127] and reductions in the final concentration of higher alcohols [124,130,133]. Martin et al 2018 [125] have explained the main metabolic pathways responsible for the ability of some species of Hanseniaspora/Kloeckera genera to produce benzenoids, diacetyl-acetoin, lactones, higher alcohols, acetate esters, fatty acids, and isoprenoids.…”
Section: Hanseniasporamentioning
confidence: 99%